The 2017 French presidential election: Were voters happy with their first-round vote?. Issue 4 (December 2018) - Courtin, Sébastien; Laslier, Jean-François; Lebon, Isabelle
Abstract A "walk up" survey conducted in the city of Caen between the two rounds of the 2017 French presidential election shows that more than one elector in six would like to have changed their first-round vote. Some voters faced a dilemma between strategic and expressive voting. The analysis of their motivation reveals that both types of regrets were present: many respondents wished that they had voted more strategically, and just as many wished that they had voted less strategically. Many participants also considered that they would rather have cast a blank vote in the first round rather than choosing a particular candidate.